Entrepreneurs’ Learning Skills and Strategies as Represented in the PIAAC Survey Empirical Research - Sarah M Ray; Tobin Lopes; Jill Zarestky (Adult Education Research Conference, 2019)
This study examined learning-skills and behaviors of self-employed individualsusing thePIAAC survey. Results indicate entrepreneurs use influence, negotiation skills, and apply new ideas to real-life situations more than employees.
Keywords: PIAAC; entrepreneurship; social justice; progressive adult education